Perbandingan Reaksi Pasar di AS, China dan Indonesia terhadap Perundingan Perang Dagang AS-China - Da Costa, Giovaninho Ferreira; Sukartha, I Made (E-Jurnal Akuntansi, 2020)
This study aims to examine the market reaction in the American, Chinese, and Indonesian stock markets about the announcement of the results of the US-China trade war negotiations. The events of the trade war negotiations took place on 10-11 October 2019. This research used the event study method and the purposive sampling method. The population in this study consisted of Dow 30, SSE 50 and LQ45 stock indices with a total sample of 123 companies. The study used Cumulative Abnormal Return (CAR) as a variable which was data from the Dow 30, SSE 50, and LQ45 stock indices during the event window. Based on the results of the analysis, it was found that there was a market reaction on the American, Chinese, and Indonesian stock markets on the announcement of the results of the US-China trade war negotiations. So there is information content for the event. The results also showed that there were differences in reactions between the American, Chinese, and Indonesian stock markets on the announcement of the results of the US-China trade war negotiations. Keywords: Market Reaction; Cumulative Abnormal Return; Trade War Negotiations.